Pseudomonas cold shock proteins suppress bacterial effector translocation in Nicotiana benthamiana - Cong, Shen; Li, Jun-Zhou; Zhang, Mei-Ran; Wei, Hai-Lei; Zhang, Wei (Frontiers in Microbiology, 2025)
IntroductionPlants detect the invasion of microbial pathogens through pathogen-associated molecular patterns (PAMPs). Cold shock proteins (CSPs) are a class of PAMPs specifically recognized by Solanales plants. While peptide inoculation studies have revealed the effects of CSPs, their in vivo roles remain poorly understood.MethodsA model system involving the interactions between Pseudomonas fluorescens and P. syringae pv. tomato DC3000 with Nicotiana benthamiana has been widely used to investigate the molecular mechanism of plant-microbe interactions. Here, we employed this model system to explore the in vivo roles of CSPs in modulating plant immunity by multiple genetic approaches.ResultsOur findings revealed that three highly-conserved CSPs were identified in Pseudomonas strains. Transient expression of these CSPs neither induced reactive oxygen species (ROS) production nor suppressed the hypersensitive response (HR) in N. benthamiana, however, it restricted bacterial effector translocation. Genetic analysis revealed that these CSPs did not contribute to the ROS burst or HR inhibition in vivo but were functionally redundant in suppressing effector translocation in a flagellin (FliC)-independent manner. Furthermore, we demonstrated that the suppression of effector translocation mediated by CSPs was less pronounced compared to that triggered by FliC. Additionally, inoculation with csp15 and csp22 epitopes triggered the pattern-triggered immunity-associated suppression of effector translocations.DiscussionThis study revealed the redundant roles of CSPs in suppressing bacterial effector translocation in vivo, providing deep insights into the PTI elicited by cytoplasmic bacterial proteins.